Coil Embolization of a Solitary Saccular Aneurysm of the Common Iliac Artery by the Stent Assisted Technique - Kagoshima, Akihito; Yokoyama, Hitoshi (Japanese Journal of Vascular Surgery, 2021)
A 69-year-old man who was due to undergo carotid artery stenting in our hospital’s Department of Neurosurgery was referred to our department for treatment of a saccular aneurysm of the left common iliac artery that was identified preoperatively. Due to the risk of complications from comorbidities, endovascular treatment was considered, and coil embolization by the stent-assisted technique using a bare metal stent was conducted under local anesthesia. Postoperative angiography showed that the signs of contrast within the aneurysm had disappeared, and the patient was discharged without complications on postoperative Day 2. Stent-assisted intra-aneurysmal coil filling is mainly used to treat intracranial aneurysms, and there has been no previous report of its use for a saccular aneurysm in the common iliac artery region. Endovascular treatment using stent grafts is the usual choice, but limitations may be imposed by factors such as device indications and effects on collateral circulation. This case demonstrates that procedures using a bare metal stent can provide a useful method of preserving the circulation of the internal iliac artery.